The comparative efficiency and cost effectiveness of the selected academic programs of the five state universities and colleges in Calabarzon, SY 2002-2004 - Peña, Felda Olimpia V. (Animo Repository, 2006)
This study attempted to compare and evaluate the efficiency and cost effectiveness of the selected academic programs of the five (5) SUCs in Calabarzon from SY 2002-03 to SY 2004-05. The input measure for cost efficiency was general expenditure while the input measures for outcome efficiency were the enrollees in the baccalaureate programs and full-time faculty. Both dimensions had the same output measures: number of graduates, weighted research rating, and weighted extension service rating. The indicators for cost effectiveness included school finance and education costs. The study adopted the following indicators of quality programs: success rate, retention rate, coefficient of efficiency, board exam performance and accreditation. The study employed the descriptive-evaluative and comparative method of research to assess the comparative efficiency and cost effectiveness of the selected academic programs of the 5 SUCs in Calabarzon. The descriptive method was used to determine the profile of the input and output measures of the SUCs and their selected programs. The Data Envelopment Analysis (DEA) technique was employed to evaluate the performance of the five SUCs based on the cost and outcome efficiency dimensions. An evaluation was also conducted on the levels of the cost effectiveness indicators: school finance and institutional education expenditures. Only academic programs that required professional board examinations and were accredited by the Accrediting Agency of State Colleges and Universities (AACUP) were analyzed accordingly. The apparent cohort method was used to determine the retention rate. Finally, comparison was made whether there were differences in the performance of the selected academic programs based on the indicators of quality programs. The data for the internal finance resource were derived from the audited and detailed financial statements of the SUCs, and which also provided the basis for determining the resource allocation priorities. School finance was obtained both from the general a